2016
DOI: 10.1016/j.ijscr.2016.03.043
|View full text |Cite
|
Sign up to set email alerts
|

An ingested mobile phone in the stomach may not be amenable to safe endoscopic removal using current therapeutic devices: A case report

Abstract: HighlightsEndoscopic removal of mobile phones in the stomach may be challenging.“Safe” removal may not be achieved using current retrieval devices.Patients consented for removal under general anaesthetic should be consented for laparotomy.Improvement in existing endoscopic retrieval devices are needed to manage similar cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…There are only three case reports published till date describing mobile phone as foreign body, two of which described the use of surgery as a definitive therapy. 6,7 The other case report is the only one till now showing endoscopic removal of mobile phone. 8 We used snare to remove mobile phone, using a technique where phone was removed along the long axis parallel to esophagus, so that there was no injury.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are only three case reports published till date describing mobile phone as foreign body, two of which described the use of surgery as a definitive therapy. 6,7 The other case report is the only one till now showing endoscopic removal of mobile phone. 8 We used snare to remove mobile phone, using a technique where phone was removed along the long axis parallel to esophagus, so that there was no injury.…”
Section: Discussionmentioning
confidence: 98%
“…Till date, there are only three case reports on mobile phone ingestion as foreign body, out of which only one showed that it could be removed endoscopically. [6][7][8]…”
Section: Introductionmentioning
confidence: 99%
“…Another case report in the literature in which a cell phone was swallowed describes a situation in which the phone was unable to be removed and thus the patient required surgical removal. It is thus prudent to ensure the patient is consented for possible surgery prior to endoscopy as the situation may change in the endoscopy suite [7].…”
Section: Discussionmentioning
confidence: 99%
“…Foreign body ingestion and food bolus impaction are frequent emergency cases in clinical practice. [1] The majority of foreign body ingestion cases occur in the pediatric population, while individuals with mental illness, neurodevelopmental disorders, alcohol intoxication, and prisoners are recognized as a high-risk adult population for foreign body ingestion. [1,2] The American Society of Gastrointestinal Endoscopy (ASGE) in 2011 and the European Society of Gastrointestinal Endoscopy (ESGE) in 2016 published clinical guidelines which addressed the management of foreign bodies in the upper gastrointestinal tract of the adult population.…”
Section: Dear Editormentioning
confidence: 99%
“…[1] The majority of foreign body ingestion cases occur in the pediatric population, while individuals with mental illness, neurodevelopmental disorders, alcohol intoxication, and prisoners are recognized as a high-risk adult population for foreign body ingestion. [1,2] The American Society of Gastrointestinal Endoscopy (ASGE) in 2011 and the European Society of Gastrointestinal Endoscopy (ESGE) in 2016 published clinical guidelines which addressed the management of foreign bodies in the upper gastrointestinal tract of the adult population. [3,4] In general, up to 90% of foreign bodies pass spontaneously, 10%-20% require endoscopic removal, while approximately 1% require surgery for extraction or treatment of developed complications.…”
Section: Dear Editormentioning
confidence: 99%